Development of Multilingual Thematic Picture Dictionary: A Support for Literacy - Suniyasih, Ni Made; Ratminingsih, Ni Made; Budasi, I Gede (Universitas Pendidikan Ganesha, 2020)
The study aimed at developing a multilingual thematic picture dictionary as a media to support literacy in English language for fifth grade elementary school students in Bali. This study used Design and Development (D&D) model by Richey and Klein (2014). The steps were (1) analysis, (2) design, (3) development, and (4) evaluation. Fifth grade elementary school students and English teachers from rural and urban area were the research subjects. They were chosen through purposeful sampling technique. In analysis, the data were collected through observation, interview, questionnaire, and document analysis. The result of needs analysis found that there is an urgency of developing multilingual thematic picture dictionary. The students needed dictionary while learning English because it helped them in finding the word’s meaning independently and could help them prepare for additional point while participating in teaching learning process content validity judgement showed that the dictionary was highly valid to criteria of a good multilingual thematic picture dictionary. The result showed that the multilingual thematic picture dictionary was categorized as ‘excellent’ media. Thus, it can be used as a media to support fifth grade elementary school students in developing their literacy skills.